COVID 19—A Spanish perspective. Issue 5 (9th September 2020) - Pérez de la Sota, Enrique; Piñón, Miguel; Quintana, Eduard; Mestres, Carlos A.
Abstract: Background: COVID‐19 hit hard worldwide. There has been an impact on global activity of cardiac surgery. Spain has been one of the hardest hit countries with one of the highest per population incidences and death. Methods: The following is an overview of the epidemiology and impact on resources, the caseload and surgical societal implemented recommendations, the description of the ECMO activity and nosocomial transmission among healthcare workers. Results: There was a reduction of 5‐6 times of the regular caseload. As of July 17, 160 ECMO implants were performed. In a 13‐center survey, at least 1 staff surgeon had SARS‐COV‐19 infection. Conclusion: Cardiac surgical activity has suffered a negative impact all over the country.